Knowledge, Attitude, and Nutritional Intervention on the Quality of Antenatal Care Among Pregnant Women - Odchigue, Conrado Jr.; Odchigue, Gloria (Journal of Interdisciplinary Perspectives, 2025)
This study explores how socioeconomic factors, healthcare system features, knowledge, attitudes, and nutritional interventions influence the quality of antenatal care (ANC) in Camiguin. A purposive sample of 300 pregnant adolescents aged 15 and below was analyzed statistically to assess these effects. Findings indicate weak and statistically negligible relationships between ANC awareness (r = 0.044, p = 0.443), visit frequency (r = 0.028, p = 0.630), and nutritional aid (r = 0.041–0.069, p > 0.05) with ANC quality. According to regression analysis, knowledge, attitudes, and eating habits only account for 1.7% of the variation (R = 0.129, R² = 0.017). This shows that more changes, such as better socioeconomic conditions, better healthcare infrastructure, and easier access to services, are needed. However, nutritional interventions significantly enhance ANC quality by fostering better health-seeking behaviors, with a second model showing a strong fit (p = .015). According to this model, attitudes about health behaviors make up 70% of the variation in ANC, while understanding prevention, awareness, and management make up 29%. The fact that attitude (p=.333) and information (p =.497) had no significant effects shows that they might have indirect effects, like support networks and developing habits. The results make it clear how important it is to deal with the social barriers, accessibility problems, and indirect pathways that affect maternal health care. Improving systemic factors could lead to better ANC quality and better health results for mothers in Camiguin.